Climate change in the media: reporting risk and uncertainty - Painter, J (Reuters Institute for the Study of Journalism, 2013)
Recent research has shown that the journalistic portrayal of the problems of climate change as ‘risks’ rather than ‘uncertainties’ can create a stronger response from the public in terms of engagement and understanding. Understanding the concepts of risk and uncertainty – and how to communicate them – is a hotly debated issue across the scientific, management and policy-making communities. In this book, James Painter analyses how the international media present the two issues of risk and uncertainty. He focuses on the coverage of recent projections of global temperatures and of the melting ice of the Arctic Sea, and includes six countries, Australia, France, India, Norway, the UK and the USA.